Capacity strengthening as a pathway to drive food systems transformation towards sustainable healthy diets: Reflections from the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) - Kruft, Krista; Herens, Marion; Namugumya, Brenda Shenute; De Groote, Bram (International Food Policy Research Institute, 2024)
Food systems are failing to provide sustainable, healthy diets that promote health, environmental sustainability, affordability, and cultural acceptability, leaving over three billion people unable to access such diets. Following calls for transformation after the 2021 UN Food Systems Summit and subsequent international dialogues, there is growing recognition of the need for systemic approaches to accelerate food systems transformation (FST). However, many stakeholders remain uncertain about how to implement effective changes, highlighting the need for sustainable development pathways that integrate health, environmental, and inclusion goals. This paper explores what capacities are needed for driving FST, emphasizing the need to strengthen skills and competencies in individuals, organizations, and societies to achieve transformative goals.